DIGITAL MANAGEMENT OF ARTS EDUCATION IN THE ERA OF INDEPENDENT LEARNING IN THE CHURCH MUSIC EDUCATION STUDY PROGRAM - Rolfi Junyanto Is Natonis; Philby Tafuakan; I Putu Ardiyasa (Prima Magistra: Jurnal Ilmiah Kependidikan, 2026)
This study analyzes digital transformation in arts education management during the Merdeka Belajar era using a qualitative approach with a case study design. The research was conducted in the Church Music Education Study Program at IAKN Kupang. Data were collected through in-depth interviews, participatory observation, and document review. The findings reveal that digital transformation planning includes needs assessment, curriculum adjustment, and teacher capacity development. The implementation of digital-based arts learning transforms teachers into facilitators, expands online collaboration, and applies electronic portfolio evaluation. An effective digital governance model is participatory, characterized by visionary leadership and a transparent evaluation system. Digital transformation aligns with the Merdeka Belajar policy, emphasizing flexibility, creativity, and project-based learning. Successful implementation depends on infrastructure readiness, teacher competency, and sustainable policy support. Recommendations include strengthening teachers' digital literacy and ensuring equitable access to technology by the government. This study contributes to understanding how church music education programs can adapt to digital transformation while maintaining their unique characteristics of integrating theological, liturgical, and musical values.